PENGARUH PERTUMBUHAN EKONOMI DAN UPAH BURUH TERHAP TINGKAT KEMISKINAN DI PULAU SUMATERA - Rati Santika; Hijri Juliansyah (LPPM UNIMAL, 2022)
This study examined and analyzed the effect of economic growth and labor wages on the poverty rate of Sumatra Island. This study used secondary data from 2015 to 2019. The data analysis method used was panel data regression using Eviews 10. The results partially showed that economic growth had no significant effect on the poverty rate of Sumatra Island. Meanwhile, labor wages had a negative and significant effect on the poverty rate of Sumatra Island.